The Beatles on Film Analysis of Movies, Documentaries, Spoofs and Cartoons - Reiter, Roland (Film, 2008)
This book provides the production history and a contextual interpretation of The Beatles' movies (A Hard Day's Night, Help!, Yellow Submarine, Let It Be) and describes their ability to project the group's image at different stages in their career. It also includes a discussion of all of The Beatles' promotional films and videos, as well as their television cartoon series and the self-produced television special Magical Mystery Tour. Along with The Beatles' feature movies and promos, this analysis also contains documentaries, such as The Compleat Beatles and Anthology, as well as dramatizations of the band's history, such as Backbeat, The Hours and Times, and Two of Us.